Synthesis and polymerization of new phosphonated monomers for dental applications - Yeniad, Bahar. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Three novel phosphonated monomethacrylate monomers have been synthesized and studied for their potential use as monofunctional reactive diluents in dental materials. The monomers are based on glycidyl methacrylate (GMA) and are synthesized (i) via reaction of GMA and (diethoxy-phosphoryl)-acetic acid (monomer 1) (ii) via reaction of GMA and (2-hydroxy-ethyl)-phosphonic acid dimethyl ester (monomer 2) (iii) via reaction of monomer 2 and diethylchlorophosphate (monomer 3). In addition a novel phosphonated dimethacrylate monomer (monomer 4) has been synthesized for the potential use in dental composites. It was prepared by the reaction of Bisphenol A diglycidylether (DER) with (diethoxy-phosphoryl)-acetic acid and subsequent conversion of the resulting diol to the dimethacrylate with methacryloyl chloride. Hydrolysis of this monomer with trimethylsilyl bromide (TMSBr) gave a new phosphonic acid-containing monomer (monomer 5) which can be used in dental adhesive formulations. The homopolymerization and copolymerization behaviors of the synthesized monomers with glycerol dimethacrylate (GDMA), triethylene glycol dimethacrylate (TEGDMA) and 2,2-bis[4-(2-hydroxy-3-methacryloyloxy propyloxy) phenyl] propane (Bis-GMA) were investigated using photodifferential scanning calorimetry at 40 ºC using 2,2’-dimethoxy-2-phenyl acetophenone (DMPA) as photoinitiator. It was found that monomer 1 and 2 homo- and copolymerize rapidly giving approximately more than 90 per cent conversion within 60 s of UV exposure. In addition to fast rate and high conversion, crosslinked polymers were obtained. These monomers also showed high crosslinking tendencies during thermal bulk and solution polymerizations. Therefore these monomers will show the advantageous properties of crosslinked systems such as great hardness and good resistance to organic solvents, chemicals and UV radiation. Monomer 3 also showed very similar reactivity to monomer 2 in homopolymerization resulting 90 per cent conversion. As a result these novel mono-functional (meth)acrylates can be used as reactive diluents to improve the cure efficiency, material properties and binding ability of dental composites. The polymerization reactivity of monomer 4 was found to be comparable to commercial dental monomers such as Bis-GMA, TEGDMA and GDMA with higher conversion (more than 70 per cent) than both Bis-GMA and GDMA although it has very rigid and bulky structure, which is very desirable for dental composites.
Keywords: Phosphonates.; Monomers.; Photopolymerization.